Genome-wide identification, characterization, evolution, and expression pattern analyses of the typical thioredoxin gene family in wheat (Triticum aestivum L.) - Zhou, Jianfei; Song, Tianqi; Zhou, Hongwei; Zhang, Mingfei; Li, Nan; Xiang, Jishan; Zhang, Xiaoke (Frontiers in Plant Science, 2022)
Typical thioredoxin (TRX) plays an important role in maintaining redox balance in plants. However, the typical TRX genes in wheat still need to be comprehensively and deeply studied. In this research, a total of 48 typical TaTRX genes belonging to eight subtypes were identified via a genome-wide search in wheat, and the gene structures, protein conserved motifs, and protein 3D structures of the same subtype were very similar. Evolutionary analysis showed that there are two pairs of tandem duplication genes and 14 clusters of segmental duplication genes in typical TaTRX family members; TaTRX15, TaTRX36, and TaTRX42 had positive selection compared with the orthologs of their ancestral species; rice and maize have 11 and 13 orthologous typical TRXs with wheat, respectively. Gene Ontology (GO) analysis indicated that typical TaTRXs were involved in maintaining redox homeostasis in wheat cells. Content estimation of ROS, the determination of antioxidant enzyme activity, and gene expression analysis suggested that TRX plays an important role in maintaining redox balance. A predictive analysis of cis-acting elements in the promoter region showed that typical TaTRXs were extensively involved in various hormone metabolism and response processes to stress. The results predicted using public databases or verified using RT-qPCR show that typical TaTRXs were able to respond to biotic and abiotic stresses, and their expression in wheat was spatiotemporal. A total of 16 wheat proteins belonging to four different families interacting with typical TaTRXs were predicted. The above comprehensive analysis of typical TaTRX genes can enrich our understanding of this gene family in wheat and provide valuable insights for further gene function research.